Clinical application value of CT portal venography in collateral circulation with portal hypertension - WU Zhe, TANG Yi, GUO Jun, SUN Hao, JIN Zheng-yu (Jichu yixue yu linchuang, 2021)
Objective To evaluate the value of computed tomography portal venography(CTPV) in displaying portal hypertension, and to analyze the imaging findings and related clinical value of different types of portosystemic shunts caused by portal hypertension. Methods A total of 159 patients with portal hypertension were selected from Fushun Central Hospital, including 110 males and 49 females. CT three-dimensional imaging of portal vein was performed at the same time. A total of 297 cases of meaningful shunt branches were selected, and the effects of other shunt branches on esophageal mucosal shunt branches were analyzed. Results All 159 patients had different types of portosystemic communication shunts caused by portal hypertension, including gastric vein group 79.5%(236/297), left renal vein group 7.7%(23/297), umbilical vein recanalization 7.1%(21/297), portal cavernous transformation 2.7%(8/297), intrahepatic shunt 0.7%(2/297) and retroperitoneal group 2.4%(7/297).In most cases, there were two or more types of communicating shunt, the draining vein and shunt branches were clearly dis- played by a three-dimensional imaging of CT portal vein. Conclusions Three-dimensional CT portal vein imaging can show the classification, location, extent and degree of collateral circulation caused by portal hypertension, and effectively track the path of abnormal blood flow, which has important guiding significance for clinical evaluation of the risk of gastrointestinal bleeding and treatment.